2012
DOI: 10.1186/1746-6148-8-184
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for porcine reproductive and respiratory syndrome virus infection and resulting challenges for effective disease surveillance

Abstract: BackgroundThis study aimed to identify risk factors for active porcine reproductive and respiratory syndrome virus (PRRSV) infection at farm level and to assess the probability of an infected farm being detected through passive disease surveillance in England. Data were obtained from a cross-sectional study on 147 farrow-to-finish farms conducted from April 2008 – April 2009. The risk factors for active PRRSV infection were identified using multivariable logistic regression analysis. The surveillance system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 37 publications
4
41
1
5
Order By: Relevance
“…This varied when regional pig density and use of vaccination were considered, with farms in a low pig density area and not using a vaccine having the lowest detection probability. Sensitivity analysis conducted in that study showed that an important parameter, as expected, was the probability that an infected pig would show clinical signs [9]. In a different context, during detection of the PRRS outbreak in Sweden in 2007 [20], active surveillance had a major role, and that particular outbreak was detected from the annual surveillance program and not due to clinical suspicion, even though animals from the whole country were naïve to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…This varied when regional pig density and use of vaccination were considered, with farms in a low pig density area and not using a vaccine having the lowest detection probability. Sensitivity analysis conducted in that study showed that an important parameter, as expected, was the probability that an infected pig would show clinical signs [9]. In a different context, during detection of the PRRS outbreak in Sweden in 2007 [20], active surveillance had a major role, and that particular outbreak was detected from the annual surveillance program and not due to clinical suspicion, even though animals from the whole country were naïve to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Proximity of infected herds has been considered a hazard, resulting in an increased risk of introduction of the virus by aerosol transmission [101, 112, 113]. Nevertheless, the airborne transmission of PRRSV and its implication on the area spread of the disease seems to be dependent on the strain and on environmental factors.…”
Section: Prrsv Transmission Between Farmsmentioning
confidence: 99%
“…In another cross-sectional study 147 of risk factors for PRRSV circulation in swine herds in the United Kingdom, > 15,000 pigs in a 10-km (6.25-miles) radius, collecting dead pigs (as opposed to incineration of pig carcasses), use of a live PRRSV vaccine, and weaning pigs at 21 to 27 days of age (as opposed to weaning at > 28 days of age) were risk factors for PRRSV circulation. Access of a rendering truck to a pig site as well as absence of a shower at the entrance to the pig site were positively associated with the PRRSV status of sow herds in a Quebec region.…”
Section: Control and Elimination Programs At The Farm Levelmentioning
confidence: 99%